Study on the stability of PT, aPTT, and fibrinogen in lyophilized plasma for external quality control - Nguyen, Thi Hong; Tran, Thanh Tung; Huynh, Thi Diem Phuc; Vu, Huy (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The stability of PT, aPTT, and fibrinogen in lyophilized fresh plasma is an important topic in medical research and applications, especially in quality control programs and coagulation testing. To study the stability of PT, aPTT, and fibrinogen indices in lyophilized plasma according to the ISO 13528 and ISO 33405 standards, applied to the external quality assessment program for coagulation.Methods: An experimental study on external quality control samples of lyophilized plasma with PT, aPTT, and fibrinogen indices. Fresh frozen plasma from the Blood Hospital was negative for HBV, HCV, HIV, malaria, and syphilis. The t-test assessed sample stability at different time points and temperatures. 200 samples were produce for each lot. Picking randomly total 35 samples for checking stability. The automatic coagulation analyzer CS-2000i from Sysmex was used. Using One-way ANOVA and t-test.Results: Lyophilized plasma containing PT, aPTT, and fibrinogen indices maintained stability when stored at temperatures of 2-8°C and -20°C for up to 3 months, with stability during transport for up to 7 days.Conclusions: Lyophilized plasma containing PT, aPTT, and fibrinogen indices maintained stability when stored at two temperatures, 2-8°C and -20°C, and remained stable during transportation throughout the study period.